A Proposed Algebra Assessment for Use in a Problem-Analysis Framework. (June 2017) - Walick, Christopher M.; Burns, Matthew K.
Algebra is critical to high school graduation and college success, but student achievement in algebra frequently falls significantly below expected proficiency levels. While existing research emphasizes the importance of quality algebra instruction, there is little research about how to conduct problem analysis for struggling secondary students. This article proposes an assessment model designed to analyze algebra skills for struggling students to assess basic skills in mathematics, algebraic thinking, and algebra content knowledge. Results of the study indicated sufficiently reliable data. Exploratory factor analysis of the data also found three separate factors (basic calculation skills, mathematics application, and algebra content knowledge) that underlie the data. Implications for the classroom, future research, and study limitations are discussed.